Key Factors for Successful Implementation of a Sustainability Strategy - Kathrin Günther (Journal of Applied Leadership and Management, 2016)
What are the key factors for a successful implementation of a sustainability strategy?
Keywords: 650; Sustainability Strategy; implementation; key factor